Is the case for economic and monetary union in the Caribbean realistic? - Anthony, Myrvin L. (2000)
Examines some of the evidence on the suitability of the members of CARICOM to form a currnecy union. Discusses whether the proposed Caribbean Monetary authority will be able to impose successfully monetary and fiscal discipline on the members of the union. Examines whether it is likely that a common currnecy would enhance the process of closer economic integration among participating countries. Looks art the possibility of adopting the US dollar as the common currency within the union.